2020
DOI: 10.3390/antiox9080763
|View full text |Cite
|
Sign up to set email alerts
|

S-Thiolation Targets Albumin in Heart Failure

Abstract: Human serum albumin (HSA) is associated with several physiological functions, such as maintaining oncotic pressure and microvascular integrity, among others. It also represents the major and predominant antioxidant in plasma due to the presence of the Cys34 sulfhydryl group.In this study, we assessed qualitative and quantitative changes in HSA in patients with heart failure (HF) and their relationship with the severity of the disease. We detected by means of mass spectrometry a global decrease of the HSA conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 44 publications
3
25
0
Order By: Relevance
“…Still, when considering the incompatibility of the use of reducing agents with the analyses of mixed disulfides on Cys34, the addition of other analytical methods that complement bottom-up proteomics would be more desirable. Brioschi et al analyzed small thiol compounds originally bound to serum ALB as mixed disulfides [ 13 ]. These compounds were released by treating serum ALB with a reducing agent tris(2-carboxyethyl)phosphine, and they were then derivatized with 4-[2-(dimethylamino)ethylaminosulfonyl]-7-chloro-2,1,3-benzoxadiazole (DAABD-Cl).…”
Section: Analytical Chemistry Of Serum Alb Redox Statementioning
confidence: 99%
See 1 more Smart Citation
“…Still, when considering the incompatibility of the use of reducing agents with the analyses of mixed disulfides on Cys34, the addition of other analytical methods that complement bottom-up proteomics would be more desirable. Brioschi et al analyzed small thiol compounds originally bound to serum ALB as mixed disulfides [ 13 ]. These compounds were released by treating serum ALB with a reducing agent tris(2-carboxyethyl)phosphine, and they were then derivatized with 4-[2-(dimethylamino)ethylaminosulfonyl]-7-chloro-2,1,3-benzoxadiazole (DAABD-Cl).…”
Section: Analytical Chemistry Of Serum Alb Redox Statementioning
confidence: 99%
“…Binding affinities for lipid mediators also differs between reduced and oxidized serum ALB isoforms; proatherosclerotic lipids such as lysophosphatidylcholine and lysophosphatidic acid have higher affinities for oxidized ALB isoform, while anti-atherosclerotic mediators derived from eicosapentaenoic acid and docosahexaenoic acid possess higher affinities for reduced ALB isoform [ 12 ]. Furthermore, ALB oxidation (the increased HNA-1 level) was accompanied by decreased anti-oxidative activity as measured by a total radical-trapping antioxidant parameter assay [ 13 ]. The oxidation of biological components such as proteins, lipids, carbohydrates and DNA proceeds when anti-oxidative potential is attenuated.…”
Section: Introductionmentioning
confidence: 99%
“…In healthy young persons, ≈70% and ≈30% of HSA presents Cys34 as a free sulfhydryl group and as a reversible mixed disulfide with other thiols of low molecular weight, respectively [ 109 ]. On the other hand, Brioschi et al found that S-thiolation of HSA was augmented in the plasma of heart failure patients, particularly in high severity cases (class III and class IV according to the New York Heart Association classification) [ 110 ]. In addition, the authors found that S-thiolated HSA correlated with deficient antioxidant activity in plasma, suggesting that S-thiolation promoted changes in HSA at the structure and function level [ 110 ].…”
Section: Other Modifications Of Albuminmentioning
confidence: 99%
“…On the other hand, Brioschi et al found that S-thiolation of HSA was augmented in the plasma of heart failure patients, particularly in high severity cases (class III and class IV according to the New York Heart Association classification) [ 110 ]. In addition, the authors found that S-thiolated HSA correlated with deficient antioxidant activity in plasma, suggesting that S-thiolation promoted changes in HSA at the structure and function level [ 110 ]. Similar results were found in eight end-stage renal disease patients with at least 3 months of hemodialysis, observing an increase in pre-dialysis S-thiolation levels of HSA compared to control patients.…”
Section: Other Modifications Of Albuminmentioning
confidence: 99%
“…quinones and unsaturated aldehydes) [ [31] , [32] , [33] , [34] , [35] ]. Increased levels of these modified forms are associated with smoking, aging, and multiple acute and chronic diseases [ [36] , [37] , [38] , [39] ].…”
Section: Introductionmentioning
confidence: 99%